Indigenous archaeology in the Philippines decolonizing Ifugao history - Acabado, Stephen B.; Martin, Marlon (2022)
"This book illustrates how descendant communities can take control of their history and heritage through active collaboration with archaeologists. Drawing on the Philippine Cordilleran experiences, Indigenous Archaeology in the Philippines discusses how changing historical narratives help empower peoples who are traditionally ignored in national histories"